2017
DOI: 10.1038/leu.2017.275
|View full text |Cite|
|
Sign up to set email alerts
|

S1PR1 drives a feedforward signalling loop to regulate BATF3 and the transcriptional programme of Hodgkin lymphoma cells

Abstract: The Hodgkin/Reed-Sternberg (HRS) cells of classical Hodgkin lymphoma (HL) are characterised by the aberrant activation of multiple signalling pathways. Here we show that a subset of HL displays altered expression of sphingosine-1-phosphate (S1P) receptors (S1PR). S1P activates phosphatidylinositide 3-kinase (PI3-K) in these cells that is mediated by the increased expression of S1PR1 and the decreased expression of S1PR2. We also showed that genes regulated by PI3-K signalling pathway in HL cell lines significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 56 publications
(76 reference statements)
7
26
0
1
Order By: Relevance
“…Sphingosine 1 Phosphate Receptors (S1PR1-5) represent a family of G-protein coupled receptors that bind the sphingolipid (S1P) and influence migration and survival pathways in a variety of cell types; S1PRs are emerging as biomarkers in B cell lymphomas 36 and B cell development 7 . Our prior work, which demonstrated S1PR1 expression in a subset of Classic Hodgkin Lymphoma cases 8 , has recently been supported by others 9 . Additional studies indicate that S1PR expression may influence anatomic location/distribution in a variety of types of lymphoma 10 .…”
Section: Introductionsupporting
confidence: 67%
“…Sphingosine 1 Phosphate Receptors (S1PR1-5) represent a family of G-protein coupled receptors that bind the sphingolipid (S1P) and influence migration and survival pathways in a variety of cell types; S1PRs are emerging as biomarkers in B cell lymphomas 36 and B cell development 7 . Our prior work, which demonstrated S1PR1 expression in a subset of Classic Hodgkin Lymphoma cases 8 , has recently been supported by others 9 . Additional studies indicate that S1PR expression may influence anatomic location/distribution in a variety of types of lymphoma 10 .…”
Section: Introductionsupporting
confidence: 67%
“…The complex interactions of sphingolipids with nuclear gene regulation suggest close links between these pathways, but detailed understanding is missing. The ability of the sphingosine mimetic drug FTY720/fingolimod to modulate gene expression in neurons and astrocytes [38,39] is probably due in large part to the links observed between S1P receptor signaling and the activities of crucial transcription factors including NF-κB, Yin-Yang-1, or Notch [71][72][73][74][75]. However, the inhibition of class I HDACs by FTY720 / FTY720P must also be considered a potential mechanism [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…Re-analysis of two large expression datasets confirmed the down-regulation of S1PR2 in DLBCL compared to normal GC B cells, and showed that this was particularly pronounced in ABC-DLBCL ( Figure 3A) [38,[41][42][43]. To study the relationship between the expression of S1PR2 and LMP1 in primary tumours we performed IHC using an antibody that we previously showed is specific for S1PR2 [46]. In contrast to GC B cells which expressed S1PR2, 114/167 DLBCL showed no tumour cell S1PR2 expression ( Figure 3B).…”
Section: Down-regulation Of S1pr2 In Lmp1-expressing Primary Dlbclmentioning
confidence: 74%
“…Green, UK; NEL791001KT) [46]. Antibody stripping by microwaving in pH 6 citrate buffer was used between steps.…”
Section: Protein Analysis and In Situ Hybridizationmentioning
confidence: 99%